CONSTRUCTION OF IN SILICO STRUCTURE-BASED SCREENING TOOLS TO STUDY THE OXIDATIVE METABOLITES FORMATION OF CURCUMIN BY HUMAN CYTOCHROME 450 3A4 - Dewi Setyaningsih; Muhammad Radifar; Yosi Bayu Murti; Enade Perdana Istyastono (Indonesian Journal of Pharmacy, 2013)
Cytochrome P450 3A4 (CYP3A4) is a phase 1 metabolism enzyme which is responsible for the metabolism of about 3040% drug in the market. This CYP3A4 is the most abundant CYP450 expressed in human body and also the one who is responsible for the biotransformation of most drugs. The competitive inhibition of curcumin (a yellow bioactive pigment discovered in Curcuma sp.) towards human CYP3A4 indicates that curcumin can be a substrate for the enzyme. In this study, in silico approaches employing molecular docking and interaction fingerprinting were used to predict the binding mode and the site of metabolism (SOM) of curcumin. Together with the SOMs retrieved previously and the list of possible reactions catalyzed by CYP3A4, the docking and fingerprinting results indicate that the most probable metabolite of curcumin metabolism by human CYP3A4 is an oxidative metabolite 1-(3,4-dihydroxyphenyl)-5hydroxy-7-(4-hydroxy-3-methoxy-phenyl)hepta-1,4,6-trien-3one.Key words: site of metabolism (SOM), curcumin, biotransformation, in silico, molecular docking, protein-ligand interaction fingerprinting